Generation of a gene-corrected isogenic human iPSC line (CSUASOi006-A-1) from a retinitis pigmentosa patient with heterozygous c.5792C > T mutation in the PRPF8 gene - Sun, Xihao; Liang, Yuqin; Duan, Chunwen; Liu, Xujie; Zhou, Yalan; Mao, Shengru; Cui, Zekai; Gu, Jianing; Ding, Chengcheng; Chen, Jiansu; Tang, Shibo (Stem cell research, 2024)
Retinitis pigmentosa (RP) is a common inherited retinal disease characterized by progressive degeneration of the retina, leading to night blindness, progressive vision loss, and constriction of the visual field. Previously, we established a human induced pluripotent stem cell line (CSUASOi006-A) from a RP patient carrying heterozygous PRPF8 (c.C5792T) mutation. Here, we corrected the mutation sites in PRPF8 (c.C5792T) using an adenine base editor and then generated an isogenic control (CSUASOi006-A-1), which is a valuable cell resource for research of RP.